تسامُح الإسلام في العهدة العمرية: دراسة تحليلية Tolerance of Islam in Umar Assurance: An Analytical Study - سعيد (Zana Mohammed Ameen) زانا محمد أمين; مصطفى (Maziah Mustapha) مزية (At-Tajdid - Intellectual Refereed Journal, 2017)
مستخلص البحث يتناول هذا البحث موضوع تسامُح الإسلام مع نصارى القدس في زمن الخليفة عمر بن الخطاب t، وذلك من خلال المعاهدة التي كتبها الخليفة لأهل القدس، والتي تسمّى (العهدة العمرية)، فيُركز على حقوق النصارى، وواجباتهم في بنودها، ومدى تسامُح الإسلام فيها، وقد اعتمد البحث على المنهجين التاريخي والاستقرائي في نقل النص الأصلي للعهدة العمرية، والإتيان بما يُؤيده من نصوص الكتاب والسنة والأحداث التاريخية، وعلى المنهج التحليلي في مناقشة النصوص والوقائع التاريخية وتفسيرها وبيان مضامينها، وبيان مايصلح منها للاستدلال وما لا يصلح، ومناقشة الآراء المختلفة وترجيح الأقوى منها، وذلك كلُّه وفقًا للقواعد والضوابط التي وضعها العلماء للترجيح والقبول، وإن من أهم النتائج التي توصَّل إليها البحث أن العهدة العمرية كفلت لنصارى القدس حقوقهم الشخصية، من حفظ النفس والمال، وحقوقهم الدينية، من عدم إكراههم على الدخول في الإسلام، والحفاظ على أماكن عبادتهم، وحقوقهم الاقتصادية، من حقهم في التملك والكسب، وتكمن أهمية هذا البحث في إثبات سماحة الإسلام مع النصارى في زمن الخليفة الثاني، وذلك لمعالجة التصورات الخاطئة بين المسلمين في معاملة الخليفة مع أهل الذمة في زمانه، وذلك اعتمادًا منهم على ما لا يصح ثبوته. Abstract This research attempts to elucidate the subject of tolerance of Islam with Christians of Jerusalem during the caliphate of Umar bin al-Khaṭṭāb in the light of his treaty, which is known as “Umar’s Assurance to the People of “Aelia” (al-’Uhdah al-Umariyyah). This treaty expounds the rights and duties of Christians and Islamic tolerance towards them. The researcher adopts historical and inductive methods for the transmission of original texts of al-’Uhdah al-Umariyyah and elaboration of it in the light of the Quran, Ḥadith and historical facts. Likewise, the analytical method is employed for discoursing on texts and deliberating on relevant historical events. Furthermore, it distinguishes those articles of al-’Uhdah al-Umariyyah which are eligible for inference from that which are ineligible followed by discussion of differed opinions and preference of preponderant one from them conforming to the authentic maxims and rulings. This research is concluded with several significant findings and one of them is that this treaty guaranteed the preservation of personal rights of Christians of Jerusalem such as protection of their body and property, and their religious privileges. This treaty assures that they should not be forcibly converted to Islam but their churches should be protected. Moreover, it guarantees their financial rights in terms of ownership of property and its collection. This research is deemed particularly significant because it establishes the tolerance of Islam with Christians during the period of second Caliph, which is conducive to remove the misconceptions based on unproven facts among Muslims about how Caliph treated non-Muslim citizens of Islamic state. Keywords: Tolerance, Umar bin al-Khattab, Jerusalem, al-’Uhdah ’Umariyyah, ahl al-dhimmah. Abstrak Kajian ini membincangkan topik toleransi Islam terhadap orang kristian Baitulmaqdis pada zaman pemerintahan Umar bin Al-Khattab r.a, iaitu melalui perjanjian yang ditulis oleh khalifah kepada penduduk Baitulmaqdis yang dinamakan ‘Perjanjian Umar’. Kajian akan menumpukan kepada hak dan kewajipan orang-orang Kristian seperti yang tertera di dalam perjanjian tersebut dan sejauh mana sikap toleransi yang ditunjukkan oleh Islam melaluinya. Dua pendekatan telah digunakan iaitu pendekatan diakronik dan induktif. Ia dilakukan dengan meneliti teks asal Perjanjian Umar dan memadankannya dengan ayat-ayat Al-Quran, hadith dan sirah yang menyokongnya. Kaedah analisa juga digunakan dalam membahaskan kandungan nas-nas dan peristiwa sejarah. Selain itu, kajian juga menjelaskan beberapa ayat yang sesuai dijadikan dalil dan yang tidak sesuai. Perbezaan pandangan dalam hal ini juga dikupas bagi menentukan pendapat yang paling kuat berdasarkan kaedah dan disiplin ilmu yang telah digariskan oleh ulama dalan masalah pentarjihan dan penerimaan. Antara dapatan penting dari kajian ini Perjanjian Umar melindungi hak-hak peribadi penganut Kristian di Baitulmaqdis seperti perlindungan nyawa dan harta, hak beragama, tiada paksaan menganut agama Islam, pemeliharaan tempat-tempat ibadah mereka, jaminan hak ekonomi serta hak pemilikan dan pendapatan. Kepentingan kajian ini boleh dilihat dari sudut menetapkan konsep toleransi Islam terhadap penganut Kristian pada zaman khalifah kedua. Hal ini penting bagi memperbetulkan salah faham oleh orang Islam berkenaan interaksi khalifah terhadap golongan zimmi pada zaman beliau kerana berpegang kepada fakta yang tidak sahih. Kata Kunci: Toleransi, Umar bin al-Khaṭṭāb, Jerusalem, al-’ahdah ’mariyyah, ahl al-dhimmah.